PENERAPAN MODEL UNIFIED THEORY OF ACCEPTANCE DAN USE OF TECHNOLOGY (UTAUT2) UNTUK MENJELASKAN BEHAVIORAL INTENTION DAN ACTUAL USAGE PENGGUNAAN APLIKASI QRIS DI KOTA MALANG - Ahmad Rifa’i; Ike Kusdyah Rachmawati; Theresia Pradiani; Widi Dewi Ruspitasari (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
Quick Response Code Indonesian Standard (QRIS)a banking service that aims to provide smoothness and convenience in banking by utilizing information technology. Research to examine the extent to which Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Perceived Value and Habit and Behavioral Intention influence on Behavioral Usage. This research is an explanatory research, the location of this study was conducted in the city of Malang, East Java. The population in this study were all people who transacted using Mobile Banking with a sample of 196 respondents. Data analysis techniques using Descriptive Statistical Analysis, Path Analysis and Testing Hypotheses. From the results of the analysis and discussion obtained the results of Performance Expectancy, Effort Expectancy, Facilitating Conditions and Hedonic Motivation significantly influence Behavioral Intention. Furthermore Social Influence, Perceived Value and Habit have no significant effect on Behavioral Intention. Facilitating Conditions and habits do not significantly influence Behavioral to Used, but Behavioral Intention influences Behavioral to Use. Facilitating Conditions and habits significantly influence Behavioral Usage through Behavioral intention.